2006
DOI: 10.1093/rpd/ncl384
|View full text |Cite
|
Sign up to set email alerts
|

Beta radiation exposure of medical staff and implications for extremity dose monitoring

Abstract: Sealed and unsealed beta radiation sources come into use to a greater extent in radiation therapy, e.g. for treating inflammatory joint diseases by radiosynoviorthesis (RSO), by injecting 90Y, 186Re or 169Er-solutions. Sealed 90Sr/90Y and 32P-sources or 188Re-liquid-filled balloon catheter are applied in vascular brachytherapy. Recently, 90Y-labelled antibodies are being successfully used in radioimmunotherapy (RIT) of malign lymphoma. Such practices require handling of high activities at small distances to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 4 publications
2
25
0
1
Order By: Relevance
“…The application of small and thin thermoluminescent dosimeters (TLDs) to the fingertips may aid to provide basic information on dose distribution across the extremities [12]. In particular, the TLDs based on a-Al 2 O 2 :C have shown to be promising thanks to their constant radiation response and good tissue equivalence at typical beta energies used in the nuclear medicine applications [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The application of small and thin thermoluminescent dosimeters (TLDs) to the fingertips may aid to provide basic information on dose distribution across the extremities [12]. In particular, the TLDs based on a-Al 2 O 2 :C have shown to be promising thanks to their constant radiation response and good tissue equivalence at typical beta energies used in the nuclear medicine applications [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The plastic holder significantly influences the beta particle range, especially at the low energy of 147 Pm. In fact a thickness of 0.5 mm of plastic material is sufficient to completely stop beta particles with an average energy of 60 keV (Rimpler and Barth 2007). In this case, the ratio E mi /C for 147 Pm is less than 0.1 for both type A and type B.…”
Section: Resultsmentioning
confidence: 93%
“…The high workload and the small number of people involved in this practice can potentially lead to high absorbed dose to the skin. In fact, if the radiation protection standard in beta-emitter handling is low and staff are unaware of the local skin dose absorbed when handling such materials, the exposure may potentially exceed the annual threshold of 500 mSv (Rimpler and Barth 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In Germany, over 60 000 RSO therapies are performed annually (35,36) . All these studies revealed that even with RSO, the highest dose is to be expected on the top of the left forefinger or thumb.…”
Section: Nuclear Medicine Therapymentioning
confidence: 99%